Antimicrobial activities of stembark and wood extracts from Nauclea subdita against pathogenic microorganisms - Fatin Ruzanna Jamaludin; Lee Seng Hua; Zaidon Ashaari; Razak Wahab; Jamaluddin Mohd Daud
Aims: The aim of the study was to investigate the antimicrobial activity of Nauclea subdita (Korth) Steud against six pathogenic microorganisms.